Physical characteristics of microwave assisted moulded foam from cassava starch-corn hominy - Endang Warsiki; Evi Savitri Iriani; Randi Swandaru (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2012)
Biodegradable foam is a packaging material made from renewable resources which is very prospective to substitute synthetic polystyrene foam. Starch is now dominantly use as a promising material to produce this foam due to its superior characteristic and its availability. However, starch is preferable as food source thus it is important to looking for a material such as corn hominy to reduce its usage in biopolymer production. Corn hominy is a by-product of corn milling which has high content of starch and fiber. Its high fiber content could improve the strength of the foam. This research is aimed to formulate the composition of corn hominy and cassava starch to produce good quality of biodegradable foam. Polyvinyl alcohol (PVOH) is added for further better physical properties. The physical analysis showed that the composition of cassava starch and corn hominy feed has affected physical properties of biodegradable foam. Increasing the content of starch resulted on increasing of foam expansion. In contrast, the more starch content in the foam, the more brittle the foam will be. The best composition was given by ratio of 80 %-wt cassava starch and 20 %-wt corn hominy. The adding of PVOH affected the physical properties of less hardness and less brittle of the foam. Keywords: biodegradable foam, cassava starch, hominy feed, PVOH Abstrak Busa biodegradable merupakan bahan pengemas yang terbuat dari bahan nabati, ditujukan untuk subtitusi polistirena busa sintetik. Bio-polimer ini umumnya terbuat dari pati singkong karena ketersediaannya yang melimpah dan keunggulan sifat-sifat busa pati yang dihasilkan. Bagaimanapun, singkong adalah bahan pangan, sehingga bahan lain seperti ampok jagung perlu diujicobakan untuk mengurangi penggunaan singkong pada produksi bio-polymer ini. Ampok merupakan hasil samping dari penggilingan biji jagung. Kandungan serat ampok sangat tinggi dan diyakini dapat memperbaiki sifat fisis mekanis busa seperti meningkatkan kekuatan tarik dan mengurangi kerapuhan busa. Penelitian ini bertujuan untuk memformulasi komposisi pati singkong dan ampok jagung untuk memproduksi busa biodegradable berkualitas baik. Polivinil alkohol (PVOH) ditambahkan untuk membantu memperbaiki karakter fisik busa. Hasil penelitian menunjukkan bahwa rasio pati dan ampok mempengaruhi sifat fisik mekanis busa. Peningkatan kandungan pati dalam busa akan meningkatkan sifat rapuh bahan. Komposisi terbaik dihasilkan dari busa berbahan 80%-b pati dan 20 %-b ampok. Penambahan PVOH dapat memperbaiki sifat fisik busa dengan menurunkan kekerasan dan kerapuhan. Kata kunci: busa biodegradable, pati singkong, ampok jagung, PVOH